Microteaching and Its Effects on Anxiety and Pedagogical Mental Models in Pre-Service Teachers - Yudi Hari Rayanto, Dies Nurhayati (Lembaga Bale Literasi, 2025)
Although microteaching has been widely used in teacher education to improve instructional skills, limited research has simultaneously examined its impact on both the emotional and cognitive dimensions of teacher preparation, particularly teaching anxiety and pedagogical mental model development among pre-service teachers. This study addresses this gap by investigating the effect of a microteaching intervention on reducing teaching anxiety and enhancing pedagogical mental models among pre-service teachers. Employing a quasi-experimental design, the study involved 19 sixth-semester students enrolled in the English Education Study Program at Universitas PGRI Wiranegara during the 2025/2026 academic year. Participants were assigned to an experimental group and a control group using purposive sampling. Data were collected using the Teaching Anxiety Scale (TAS), a Pedagogical Mental Model Questionnaire, and observation sheets. Descriptive statistics, paired-samples t-tests, independent-samples t-tests, and Cohen’s d effect size analysis were used to analyze the data. The results indicated that the microteaching intervention significantly reduced teaching anxiety among participants in the experimental group, as evidenced by lower post-test scores compared to those of the control group. The intervention also promoted the development of pedagogical mental models; however, the improvement was not statistically significant. Effect size analysis revealed a very large effect on teaching anxiety reduction and a medium effect on pedagogical mental model development. The novelty of this study lies in its integrated examination of microteaching as a strategy for fostering both emotional readiness and pedagogical cognition among pre-service teachers. These findings highlight the importance of incorporating reflective microteaching practices into teacher education programs to strengthen prospective teachers’ professional preparedness.